Rapid Point-of-Care Influenza Testing for Patients in German Emergency Rooms – A Cost-Benefit Analysis - Roland Diel; Albert Nienhaus (Journal of Health Economics and Outcomes Research)
**Background:** Each year, influenza causes significant morbidity and death worldwide and produces significant economic losses at the expense of the healthcare system.